Effect of welding heat input on microstructure and mechanical properties at coarse grain heat affected zone of ABS grade a steel - Wan Muda, W.S.H.; Mohd Nasir, N.S.; Mamat, S.; Jamian, S. (Asian Research Publishing Network, 2015)
The fabrication and construction of structures used in the offshore and marine industries shall be made according to the international code and standard requirements to ensure the quality and to extend the life span. Proper material selection needs to be carried out to achieve proper function and to reduce the cost. The ABS Grade A steel is one of the huge materials used in the marine industries. The study has been carried out to scrutinize the effect of welding heat input to the distribution of microstructure formation and its mechanical properties at CGHAZ of the ABS Grade A steel. Three heat input combinations designated as low heat (0.99 kJ/rnm), medium heat (1.22 Wrnrn) and high heat (2.25 kJ/mm) have been used to the weld specimen by using flux cored arc welding (FCAW) process. The microstructure formation at CGHAZ consists of grain boundary ferrite (GBF), Widmanstatten ferrite (WF) and pearlite (P). Significant grain coarsening was observed at the coarse grain heat affected zone (CGHAZ) of all the joints and it was found that the extent of grain coarsening at CGHAZ increased with the increase in the heat input. The results of the mechanical investigation indicate that the joints made using low heat input exhibit higher hardness and impact toughness value than those welded with medium and high heat input. It can be concluded that the higher the heat input, the higher the grain size of microstructure but will lead to lower hardness and impact toughness value